2016
DOI: 10.1292/jvms.16-0289
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of pathogenic <i>Leptospira</i> spp. among large ruminants in the Philippines

Abstract: The extent of Leptospira infection in large ruminants resulting to economic problems in livestock industry in a leptospirosis-endemic country like the Philippines has not been extensively explored. Therefore, we determined the prevalence and carrier status of leptospirosis in large ruminants using molecular techniques and assessed the risk factors of acquiring leptospirosis in these animals. Water buffalo and cattle urine samples (n=831) collected from 21 farms during 2013–2015 were subjected to flaB-nested PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Similarly, sequence analysis of Leptospira flaB in large ruminants revealed the formation of three major clusters with L. borgpetersenii or L. kirschneri and molecular epidemiology based on this gene clarified the main source of leptospires for other farms (Villanueva et al . 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, sequence analysis of Leptospira flaB in large ruminants revealed the formation of three major clusters with L. borgpetersenii or L. kirschneri and molecular epidemiology based on this gene clarified the main source of leptospires for other farms (Villanueva et al . 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Restriction fragment length polymorphism of the PCR product of this gene was successfully used to discriminate between Leptospira species in the laboratory (Kawabata et al 2001) and was also used in field settings to study the molecular epidemiology of canine leptospirosis in Japan (Koizumi et al 2013). Gamage and colleagues 2012 borgpetersenii or L. kirschneri and molecular epidemiology based on this gene clarified the main source of leptospires for other farms (Villanueva et al, 2016).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while cattle association was high with several Leptospira species, water buffalo association was high only with L. borgpetersenii suggesting a more restricted host preference for this species in Sri Lanka (Fig 4). L. borgpetersenii have been associated with water buffalo in several reports [60,61]. Since large mammals that excrete much more urine than rats shed significantly more Leptospira per day, our results suggested that large mammals are the main contaminating source of irrigation water in Kandy.…”
Section: Discussionmentioning
confidence: 51%
“…L . borgpetersenii have been associated with water buffalo in several reports [ 60 , 61 ]. Since large mammals that excrete much more urine than rats shed significantly more Leptospira per day, our results suggested that large mammals are the main contaminating source of irrigation water in Kandy.…”
Section: Discussionmentioning
confidence: 99%